Breastfeeding Promotion in German Maternity Hospitals and Consecutive Rates of Exclusive Breastfeeding During the First 4 Months of Life – The Prospective SuSe II Study. (7th June 2021) - Hockamp, Nele; Hülk, Philipp; Lücke, Thomas; Kersting, Mathilde
Abstract: Objectives: The implementation of the "10 Step" programme of WHO/UNICEF for breastfeeding promotion (BFP) in maternity hospitals is considered as a key for long-term breastfeeding success of mothers worldwide. The objective of this work was to determine whether this expectation also holds true for Germany. Methods: The nationwide SuSe II study (2017–19) is a combination of a cross-sectional survey in maternity hospitals and a prospective follow-up of mother-infant pairs (0.5, 2, 4, 6, 12 months postpartum (pp)) recruited in the participating hospitals. All German maternity hospitals were invited to complete an online questionnaire assessing BFP based on the 10 Steps. Mothers reported if they were breastfeeding and if the infant received any other fluid or food. Relevant factors for exclusive breastfeeding (EBF) during the first 4 months pp were determined in 5 multivariable models with variable selection through backward elimination according to the likelihood ratio. Results: One hundred and three hospitals (15% out of 692) recruited 929 mothers (33% of eligible mothers) who had tried to breastfeed, with a compliance of about 90%. During hospital stay, 74% of mothers exclusively breastfed, 77% at discharge, 74% 2 weeks, 70% 2 months and 58% 4 months pp. Hospitals had implemented between 2 and 10 Steps (median 7). Until 4 months pp, the rate of EBF was higher, if mothers had given birth in hospitals with a high BFP (≥9 Steps) compared to medium (6–8 Steps) or low promotion (≤5 Steps). Even after adjusting for potential confounders, high BFP compared to medium and low promotion significantly increased the modeled odds of mothers for EBF during hospital stay (p = 0.000), at discharge (p = 0.005) and 2 months pp (p = 0.002). Maternal breastfeeding experience and absence of a pacifier significantly increased the modeled odds of mothers for EBF at all 5 time points pp. Conclusions: Implementation of at least 9 of the 10 Steps for BFP in hospitals was related to mothers' breastfeeding success in the first 2 months. It is noteworthy that this association was found even at the high level of BFP in hospitals and the high initial breastfeeding rates in the SuSe II study. Funding Sources: Funding: Federal Ministry of Food and Agriculture Client: German Society for Nutrition.